The pastoral epistles - Hanson, Anthony Tyrrell (Grand Rapids, MI Eerdmans, 1982)
Contents : 1 and 2 Timothy and Titus. Includes bibliographical references and indexes.
Keywords: Bible. N.T. Pastoral epistles -- commentaries